Prevalence and components of premorbid metabolic syndrome in workers insured by social health in an area of moderate altitude in Peru - Espinoza-Rivera, Saúl (2023)
Objective: To analyze the prevalence and components of pre-morbid Metabolic Syndrome (MS) in workers insured by social health in a moderate altitude area (Chachapoyas, Peru). Materials and methods: A cross-sectional study was conducted with data from various types of workers belonging to a program focused on diagnosing pre-morbid MS, obesity and overweight in workers in their workplaces during the period from October 2017 to August 2018. Data previously recorded by the program were used. MS was diagnosed according to the criteria of the guide "Harmonizing the Metabolic Syndrome". Results: A total of 1021 subjects were included. The overall prevalence of pre-morbid MS was 32.8% (312/952). In men, the prevalence was 35.4% (160/452) and in women 30.4% (152/500), with no statistically significant differences between sexes (p = 0.101). The frequency of the components of MS in the total population of the study was: Central obesity 73.4%, hypertriglyceridemia 45.6%, low HDL-C 66.3%, hyperglycemia 10.0% and high blood pressure 6.5%. Participants with premorbid MS were significantly older than those without pre-morbid MS (44 versus 36 years, p <0.001). Conclusions: There is a high prevalence of pre-morbid MS in workers residing in Chachapoyas, contrary to what previous evidence suggests.